PROSPECTS FOR TURMERIC AGROINDUSTRY IN LAMTEUBA, SEULIMUM SUB-DISTRICT ACEH BESAR DISTRICT - Widyawati; Rahmi Khoiriah Nasution; Anwar Deli (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
Turmeric is a medicinal plant that has many benefits. There are more turmeric production centers in Indonesia in Java and Sumatra, it does not rule out the possibility of turmeric production centers in Aceh Province, one of which is in Seulimum District. The limited knowledge possessed by turmeric farmers, both technology and the market, makes turmeric farmers prefer to sell directly their turmeric harvests rather than processing them first into other products. The purpose of this study was to determine the processing techniques, costs and benefits derived from the turmeric powder processing industry in Lamteuba, Seulimum District, Aceh Besar District. The scope of this research is limited to processing techniques, business feasibility analysis of turmeric powder. Based on the research results, it was found that the turmeric powder processing techniques in Lamteuba already used machine technology such as washing machines, slicing machines, ovens and milling machines. Production costs incurred amounting to Rp. 22,047,273/month with a monthly profit of Rp. 4,952,727. The R/C Ratio value is 1.22, meaning that the business is feasible to run. The ROI value is 22.46% and the BEP price and BEP the amount of production obtained are Rp. 48,993/Kg and 367 Kg/month. 46% and BEP price and BEP the amount of production obtained respectively Rp. 48,993/Kg and 367 Kg/month. 46% and BEP price and BEP the amount of production obtained respectively Rp. 48,993/Kg and 367 Kg/month.